ChemInform Abstract: Asymmetric Diastereoselective Synthesis of Spirocyclopropane Derivatives of Oxindole. Issue 6 (February 2015) - Oseka, Maksim; Noole, Artur; Zari, Sergei; Oeeren, Mario; Jaerving, Ivar; Lopp, Margus; Kanger, Tonis
Abstract The title reaction is based on the Michael addition of 3‐chlorooxindole (I) to unsaturated 1, 4‐dicarbonyl compounds (II) and (IV), followed by an intramolecular nucleophilic substitution.